Tracking acceleration of projectiles using photonic Doppler velocimetry - Künzel, Martin; Kučera, Jindřich; Kubát, Karel; Pachman, Jiří (Univerzita Pardubice, 2022)
One of the important issues in internal ballistics is a relation of chamber pressure to projectile velocity. In a gun barrel, the projectile gradually accelerates until it exits the muzzle end. The muzzle velocity can be measured easily but the acceleration phase is quite difficult to observe. In this paper, photonic Doppler velocimeter was used to track projectiles inside gun barrels. The projectiles were accelerated using 4.5 mm calibre CO2 gun and 7.8 mm calibre powder gun. Complete velocity profiles have been obtained for the CO2 gun projectiles. In the case of powder gun tests, only very short profiles showing initial motion of the projectiles were recorded. Problems associated with this kind of measurements are discussed.
Sledování zrychlení střel pomocí PDV
Keywords: gun barrel; velocity; internal ballistics; PDV; hlaveň; rychlost; vnitřní balistika; PDV